Legal regulation of the language issue in ukraine during a full-scale invasion russian federation - Smulska, Alla (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2023)
Introduction. Language is the main fundamental principle of the consolidation of Ukrainian society, the driver of changes in national consciousness, a tool that hardens and adds strength.In the future, the formation of national solidarity, the formation of a highly cultural linguistic personality, the education of the younger generation, and in general, perhaps, our future existence as a nation, as a people, as a country, will depend on everyone's attitude towards the Ukrainian language.The language issue has always been a field of interest: from the study of its paradoxical nature in general, to the study of political manipulations and speculations that arose every time it became profitable for someone; observation of language processes that took place in the country under the guise of "mutual influence" and "mutual enrichment", but in fact were a cover for the total fusion of most of Ukraine and the decline of the prestige of the Ukrainian language, etc.Short list of main results. The article states that the history of legislation regulating the language issue in Ukraine begins with its bans during the statelessness of Ukraine as part of the Russian Empire and other states. The reasons for the long-term dominance of the Russian language in Ukraine and its consequences include centuries-old Russification, the migration of Russians to the territory of Ukraine, the physical destruction, deportation and forced emigration of Ukrainians outside of Ukraine, the formation of a "Russian" situation, when nationally conscious Ukrainians are forced to defend themselves from migrants. A number of normative acts, the adoption of which at different times was intended to regulate the language issue in Ukraine, are listed and characterized.Conclusions. The language front is another front, but not a battlefield, but a new opportunity to defend our values. To know and communicate in Ukrainian is to protect national interests and bring our victory closer. War sets the tone. With the beginning of the full-scale Russian invasion, Ukrainians began to abandon the language of the aggressor en masse, and support for Ukraine as a single state is unprecedented in all the years of independence.